Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/1357633x14552382
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation for older people using off-the-shelf applications: acceptability and feasibility

Abstract: We investigated the feasibility of providing telerehabilitation in the home as an alternative to conventional ambulatory rehabilitation. Two groups of patients were accepted for telerehabilitation. The first group were community patients who needed rehabilitation, e.g. following a stroke, a fracture or prolonged hospital admission. The second group was from two rural nursing homes where residents were identified with a recent injury, fall or hospitalisation. Telerehabilitation employed a coaching model, with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
113
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 13 publications
7
113
0
Order By: Relevance
“…The use of ICT in healthcare has shown great potential in improving the quality of life among senior citizens [10], by facilitating support in independent living for persons with conditions such as stroke and Alzheimer's disease [11,12]. Moreover, ICT has demonstrated potential in improving communication between patients and healthcare providers [13]. Although it is still unclear how telerehabilitation services can most appropriately be rendered, it has been suggested that ICT can add value to current stroke rehabilitation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ICT in healthcare has shown great potential in improving the quality of life among senior citizens [10], by facilitating support in independent living for persons with conditions such as stroke and Alzheimer's disease [11,12]. Moreover, ICT has demonstrated potential in improving communication between patients and healthcare providers [13]. Although it is still unclear how telerehabilitation services can most appropriately be rendered, it has been suggested that ICT can add value to current stroke rehabilitation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of telerehabilitation research found a high level of patient satisfaction with telerehabilitation . Crotty et al . investigated the feasibility of providing home‐based rehabilitation to older people using ‘off‐the‐shelf’ technologies and found that patients and clinicians were generally positive about this form of service delivery, whilst gains could be made in access, frequency and intensity of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…9 A systematic review of telerehabilitation research found a high level of patient satisfaction with telerehabilitation. 12 Crotty et al 13 investigated the feasibility of providing home-based rehabilitation to older people using 'off-the-shelf' technologies and found that patients and clinicians were generally positive about this form of service delivery, whilst gains could be made in access, frequency and intensity of therapy. There are, however, very few in-depth explorations of patient experiences with home telerehabilitation programmes, with most patientcentred studies focussing on patient satisfaction using quantitative surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Delivering exercise programs via telehealth using video-conferencing may provide an alternative way to enable stroke survivors to engage in supervised exercise at home. Telehealth exercise interventions targeting fitness have proved effective and safe in other populations, including cardiac rehabilitation (Clark et al, 2015), chronic obstructive pulmonary disease (Hwang et al, 2015), cystic fibrosis (Cox, Alison, Button, Wilson, & Holland, 2015) and in the elderly (Crotty et al, 2014), and telehealth is emerging as a cost-effective alternative to providing centre-based exercise programs (Maddison et al, 2018;Southard, Southard, & Nuckolls, 2003;Whittaker & Wade, 2014). In stroke, telehealth has been used successfully to monitor vital signs (Bernocchi et al, 2016), motor recovery, depression and higher cortical function (Sarfo, Ulasavets, Opare-Sem, & Ovbiagele, 2018), and to deliver speech pathology (Hill et al, 2006), upper limb physiotherapy (Benvenuti et al, 2014) and rehabilitation exercises (Bernocchi et al, 2016).…”
mentioning
confidence: 99%